The phenomenon of dental pulp sensitivity in the formation of permanent teeth - A. Zh. Petrikas; S. A. Letunovskaya; E. V. Chestnykh; D. V. Medvedev; E. P. Zin'kovskaya; I. O. Larichkin; K. V. Kulikova (LLC "Endo Press", 2021)
Aim. То carry out a comparative assessment of the change in the pain threshold (in terms of electroodontometry), the X-ray width of the root canal in the apex area and the nature of the pain sensation of the central incisors in children aged 6.5-15 years.Materials and methods. We examined 280 teeth in 280 children from 6.5 to 15 years old (central incisors). Patients are divided by age into 5 groups: 1 - 6.5-7 years old; 2 - 7-8 years old; 3 - 9-10 years old; 4 - 11-12 years old; 5 - 13-15 years old. The patients underwent electroodontometry (EOM), to measure the sensitivity threshold of the studied tooth, the subjective sensations with EOM were assessed, and the width of the apical part of the root canal was determined, according to the data of intraoral sighting radiography.Results. The study studied the process of teething and formation of teeth in dynamics from 6.5 to 15 years in 5 age groups. Changes in electrodontometry (EOM) are significant from 140.38 цА (4.5 years) to 24.38 цА (15 years) - average data. The relationship between age and the width of the root canal in the area of the apex, which is also characterized by a gradual narrowing, has been traced. Pulp pain with EOM becomes clearer and more short-lived with age. The correlation between age and pain threshold is less pronounced (41%) than between age and apical canal width (72%). Conclusions. The main role in the sensitivity of the tooth is played by the A-delta and C nerve fibers of the pulp. The phenomenon of a decrease in the pain sensitivity threshold of permanent teeth during electrodontometry in the process of root formation due to the reaction of C-fibers was established.